The Concept of Quality in Islamic Education Management in the Development of Basic Education - Rifa’I , Ahmad; SUWANTO, SUWANTO; Syamsuri, Syamsuri; DASIM, DASIM; GUNAWAN, DEDI; ASRORI, M ACHMAD (Fakultas Tarbiyah, IAIN Fattahul Muluk Papua, 2025)
This study analyzes the application of various approaches in the learning process at Madrasah Ibtidaiyah (MI) in Indonesia, with a focus on improving the quality of Islamic education at the elementary level. Using the Systematic Literature Review (SLR) method, this study collects, analyzes, and integrates the results of studies related to the application of effective teaching methods and their impact on the quality of student learning outcomes. The main findings of this study indicate that activity-based and real-life experience approaches, as well as the integration of technology in learning, can increase students' motivation and understanding of Islamic subject matter. The use of interactive learning media and e-learning provides space for students to learn flexibly and deeply, and helps teachers deliver material in a more interesting and easy-to-understand manner. In addition, this study also highlights the importance of the role of teachers in implementing effective methods. Teachers with good pedagogical competence can create a conducive learning environment, which has a positive impact on the quality of education. The involvement of parents and the community was also found to have a significant effect on the quality of education in Madrasah Ibtidaiyah, by supporting the development of students' character. However, despite these successes, this study found challenges related to limitations in facilities and infrastructure, especially in rural areas, which hinder the implementation of innovative methods. In conclusion, this study provides an overview that student-based approaches, teacher professional development, and parent and community involvement are essential to improve the quality of Islamic education in Madrasah Ibtidaiyah, although challenges such as limited distribution of resources and facilities remain major obstacles that need to be overcome.